F34 Anosognosia of motor deficits in Huntington's disease. (12th September 2022) - Gargallo, Francesca; Paridi, Dominga; Geminiani, Giuliano; Sorbo, Francesca Del; Silani, Vincenzo; Isaias, Ioannis; Soliveri, Paola; Girotti, Floriano
Abstract : Background: Anosognosia (unawareness) of choreic movements is relatively common in Huntington's disease (HD) although its origin is unclear. Aims: We investigated anosognosia of motor deficits in HD. Methods: Seventy-one outpatients with stage I or II HD participated. The motor section of UHDRS, the total functional capacity, a short battery of cognitive tests, the SANS and SAPS scales for negative and positive psychiatric symptoms, and the Hamilton scales for depression and anxiety were administered. A semi-structured four-point questionnaire was also administered to assess extent of motor anosognosia in daily life. Results: The patients were divided into 27 (38%) (group 1) aware of their motor symptoms (score zero on questionnaire), and 44 (62%) (group 2) with various degrees of unawareness: 29 (66%) group 2 patients scored 1, 11 (25%) scored 2, and 4 (9%) scored 3. The two groups were compared. Group 2 patients performed worse on visual search test (p = 0.04) and SANS (p = 0.02). Anosognosia correlated directly with UHDRS (r=0.32; p=0.04) and indirectly with anxiety (r=−0.33; p=0.03). When shown their motor impairments, the 4 patients with score 3 retained the delusional belief they had no impairment. Conclusions: Two thirds of our patients had motor anosognosia, with higher SANS score, indicating more severe apathetic syndrome, and worse visual search test, indicating slower cognitive processing, than non-anosognosic patients. The finding of delusional belief in patients with severe anosognosia suggests that psychiatric changes play a role in generating anosognosia in HD. HD anosognosia appears to have varied origins.